2014
DOI: 10.2147/ijn.s63414
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured lipid carrier surface modified with Eudragit RS 100 and its potential ophthalmic functions

Abstract: This study was carried out to evaluate the ocular performance of a cationic Eudragit (EDU) RS 100-coated nanostructured lipid carrier (NLC). The genistein encapsulated NLC (GEN-NLC) was produced using the melt-emulsification technique followed by surface absorption of EDU RS 100. The EDU RS 100 increased the surface zeta potential from −7.46 mV to +13.60 mV, by uniformly forming a spherical coating outside the NLC surface, as shown by transmission electron microscopy images. The EDU RS 100 on the NLC surface e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In the recent years, many research efforts have been made to develop drug delivery systems that would prolong the pre-ocular retention and promote the absorption of drugs 3 4 5 . Nanostructured lipid carriers (NLC), a second generation of solid lipid nanoparticles (SLN), based on mixture of solid lipids with spatially incompatible liquid lipids combines many features beneficial for ocular application such as controlled drug release, high drug loading, good bioavailability and excellent tolerability 6 7 .…”
mentioning
confidence: 99%
“…In the recent years, many research efforts have been made to develop drug delivery systems that would prolong the pre-ocular retention and promote the absorption of drugs 3 4 5 . Nanostructured lipid carriers (NLC), a second generation of solid lipid nanoparticles (SLN), based on mixture of solid lipids with spatially incompatible liquid lipids combines many features beneficial for ocular application such as controlled drug release, high drug loading, good bioavailability and excellent tolerability 6 7 .…”
mentioning
confidence: 99%
“…It has been used to deliver numerous vaginal antifungal, antiviral, antibacterial drugs, and other vaginal diseases in the form of nanocapsules and nanospheres [ 59 ]. Some studies have shown that Eudragit RS 100 may degrade into smaller fragments and remain in the body for a long time, leading to safety concerns as it accumulates inside the body and potentially induces immune disturbance [ 60 , 61 , 62 ]. Polyamidoamine dendrimers have been widely used in different drug delivery and biotechnology applications.…”
Section: Health Impact Of Conventional Polymer-based Materials In mentioning
confidence: 99%
“…The irritation of the eyes was scored according to the Draize scale. 29 The animals were sacrificed after the final observation, and the eyeballs were removed and stained with H&E for histopathological evaluation.…”
Section: In Vivo Ocular Compatibility Testmentioning
confidence: 99%